How effective is the addition of specific exercise therapy for patients after anterior cruciate ligament surgery? A systematic review and meta-analysis - Zhou, Hao; Qian, Jia; Xing, Yu-Mei; Cui, Long; Bu, Yi-Feng (Frontiers in Physiology, 2025)
ContextAnterior cruciate ligament (ACL) injuries are prevalent in sports and often require surgical intervention followed by rehabilitation. Several rehabilitation methods have been used for patients after ACL surgery.ObjectiveThis study aimed to assess the overall efficacy of exercise therapy in improving outcomes for patients following ACL surgery using a systematic review and meta-analysis of randomized controlled trials (RCTs).Data sourcesPubMed, Web of Science, Embase, and the Cochrane Library were searched for randomized controlled trials published from 1 January 2000 to 30 August 2024. Study quality was assessed using the Cochrane Risk-of-Bias tool.Study selectionA total of 11 randomized controlled trials (whole-body vibration training = 4, core-stability training = 2, strength training = 3, blood flow restriction training = 1, and aquatic training = 1) involving 552 anterior cruciate ligament surgery patients were included.Data extractionTwo researchers individually screened the key information for each eligible study and evaluated the quality of the studies. Any dispute was discussed by a third researcher.ResultsCompared with conventional therapy, exercise therapy significantly reduced pain scores (mean difference: −0.53, 95% CI: −0.82 to −0.24, and p < 0.001) and improved muscle strength (flexion: 13.76 and extension: 12.46) and knee function (effect size: 2.06 and p = 0.001). Secondary outcomes, although less pronounced, also demonstrated improvement.LimitationThe sources of heterogeneity among the included studies were not fully identified, particularly concerning variations in exercise protocols or patient characteristics. Additionally, the therapeutic effects of specific exercise modalities (e.g., strength training versus aquatic training) were not directly compared.ConclusionExercise therapy is effective in reducing pain, enhancing muscle strength, and improving knee function in ACL surgery patients. These findings underscore the importance of integrating tailored exercise therapies into rehabilitation programs.Systematic review registration numberhttps://www.crd.york.ac.uk/PROSPERO/, identifier registration number. CRD42023476653.